Developing Intercultural Communication and Cultural Intelligence through Intercultural Musical Contacts - Montassir Hmala (Media and Intercultural Communication: A Multidisciplinary Journal)
This article presents a scientific recording of a two -term intercultural musical experience that took place in October 2018 and March 2019 in a high school in Beaune la Rolande, France. It explores the crucial role that music can play in developing and strengthening intercultural communication (IC) and cultural intelligence (CI), specifically in intercultural educational contexts. To achieve this and drawing on Allport’s (1956) Contact Hypothesis Theory (CHT) and Bennett’s (1953) Developmental Model of Intercultural Sensitivity (DMIS), a qualitative research design was chosen, with focus group discussions; involving participating students, and semi -structured interviews with three teachers and the high school principal as the main techniques for data collection. The thematic content analysis of the data resulted in the emergence of six main themes: Anxiety/Scepticism, Resistance, Discovery, Appreciation, Openness, and Transformation. The findings of the study concretely demonstrated that exposure to forging music could have a tangible impact on students’ development of intercultural communication and cultural intelligence skills.